Flexible latex photonic films with tunable structural colors templated by cellulose nanocrystals. Issue 9 (21st February 2018) - Leng, Junxiao; Li, Guihua; Ji, Xingxiang; Yuan, Zaiwu; Fu, Yingjuan; Li, Hongguang; Qin, Menghua; Moehwald, Helmuth
Abstract : Free-standing latex films were prepared by using CNCs as templates. The structural color of the latex film shows a reversible response to water adsorption and dehydration. The maximum elongation at break of the latex film reaches 34.5%, which is ∼8 times larger than that of the best film reported so far. Abstract : Fabrication of nanostructures with multiple functions templated by cellulose nanocrystals (CNCs) has become very attractive, and chiral structures fabricated via evaporation-induced self-assembly (EISA) have become particularly important for building photonic films. However, films obtained so far suffer from low mechanical strength, which significantly hinders their applications. Here, we report a facile way to obtain highly flexible latex films with tunable structural colors via CNC templating. First, composite films (CFs) containing silicone-modified acrylic latexes (SALs) and CNCs were prepared via EISA. At mixing ratios of SALs to CNCs of 0.2–0.4, homogenous films were obtained, where the latexes cohere together to form a network. After alkali treatment followed by rinsing with water or alcohol, CNCs could be removed, leading to the formation of free-standing latex films. The chiral nematic (N*) structure originating from the organization of CNCs via EISA was retained in the latex film, leading to the preservation of the structural color. Due to a reduced helical pitch caused by the deformation of the porous latex network during the removal of CNCs and the subsequent drying process, the reflection of the film could be blue shifted, and the extent was closely related to the type of solvent used during rinsing. Interestingly, the structural color of the latex film could be reversibly tuned by water adsorption and dehydration, which could be ascribed to the expansion/shrinking of the porous latex network. The flexibility of the pores in expansion/shrinking also effectively released the internal stress of the film when it was stretched and/or deformed. This feature, combined with the intrinsic flexibility of the backbones formed by the crosslinking of SALs, imparts the film impressive mechanical strength. The maximum elongation at break reached 34.5%, ∼8 times larger than that of the best film reported so far.